Green synthesis of a Schiff base ligand and its Co(II), Cu(II) and Zn(II) complexes: thermoanalytical and spectroscopic studies - Moura, Aniele de [UNESP]; Júnior, José Benedito [UNESP]; Carvalho, Ana Carina Sobral [UNESP]; Caires, Flávio Junior [UNESP] (Springer Nature, 2022)
Schiff bases are organic compounds that present a broad biological activity, which can be improved by the coordination with different metal ions. Their complexes can also act as corrosion inhibitor agents or even as heterogeneous catalysts in organic reactions. Based on the Schiff base synthesis versatility, and its several potential applications, this work focused on the obtention of a Schiff base derived from 4-aminosalicylic acid and salicylaldehyde by the mechanochemical method, and its Co(II), Cu(II), and Zn(II) complexes by precipitation in an aqueous solution. Using eco-friendly methods, it was not necessary to employ organic solvents or heating in the syntheses. Spectroscopic techniques were used to characterize the structure of the Schiff base and its coordination compounds, among them, MS, FTIR, UV/VIS/NIR, thermoanalytical techniques (TG-DSC, DSC, and EGA), and X-ray powder diffraction. The spectroscopic and thermal results confirmed Schiff base formation, and by the thermoanalytical study, it was possible to evaluate its thermal behavior and propose a thermal degradation mechanism, which results in the formation of a decarboxylation, resulting in the 3-aminophenol, a common thermal product of 4-aminosalicylic acid. For the metal complexes, the analytical and thermoanalytical results showed that they present a 1:1 metal–ligand stoichiometry, while FTIR and UV–VIS/NIR spectra demonstrated that the ligand coordinated with the metals in different ways through the carboxylate group and the phenolic oxygen. Furthermore, the EGA results showed that during the metal complexes decomposition, salicylaldehyde releasing is common for Co(II) and Zn(II) complexes, which is resulted from the C–N bond break. Graphical abstract: [Figure not available: see fulltext.]
Keywords: Evolved gas analysis; Mechanochemical method; Schiff base; Thermal degradation mechanism; Transition metal complexes